Cirurgia de transgenitalização e adequação registral como mecanismos insuficientes de alcance da dignidade humana do transexual - Ramos, Roberto Leonardo da Silva (2014)
The transgenitalization surgery is a procedure used by medicine to adjust the transsexual s body to one the individual feels suitable with his or hers identity. For the surgery to happen it s necessary that a multidisciplinary team declare the transsexuality a pathology, which inflicts serious psychological suffering and reduction of the libido due to not accepting their own body. Majoritarian jurisprudence understands that after the physical modification the person may modify the civil records in order to adjust to his or hers new characteristics. After those interventions, both chirurgical and documental, this individual will have dignity. This work intends to understand if the procedures mentioned are enough to assure dignity to transsexual individuals. The main purpose here is to demonstrate society traditionally divides itself on men and women in heterosexual behavior, which translates a binary framing for people. The dissertation also clarifies that gender is a result of cultural construction, which stands in the way of a simplistic division of heterosexual behavior between men and women. It will be used a bibliographic research of the themes brought here, such as feminism, transsexuality or right to a name. As a theoretical reference it will be adopted the Marxist feminism theory. To accomplish what it proposes, this dissertation will be divided in three chapters. The first chapter will disclosure the right to a name, mentioning its principles and the legislation, both internal and international. It also clarifies about the possibilities of name change, touching especially what concerns the transsexual and, by consequence, the surgery of sexual adaptation. The second chapter approaches the feminism theory, which denaturalizes the gender debate, pointing that the relation of subjection between men and women has a political obliquity, and amplifies gender researches to involve also transsexuals. The third chapter uses the queer theory to point the necessary breaking of the binary composition of men/women and deconstruct the dominant thought that uses signs to establish the comportment pattern thought as ideal, which is called heteronormativity. In that point it is showed that both the transgenitalization surgery and the requirement of this surgery to alter social registration enforce the binary pattern of gender and it is not enough to assure dignity to those individuals that don t adapt to such a corporal dimorphism. This work then concludes that both medical and legal mechanisms aren t enough to the pretensions of dignity of transsexual individuals.